KOMUNIKASI INTERPERSONAL ANTARA PELATIH DAN ATLET BULUTANGKIS DALAM MENINGKATKAN PRESTASI PADA DINAS PEMUDA DAN OLAHRAGA (DISPORA) PROVINSI RIAU - Charles. P "; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Interpersonal communication is very important upon improvingachievement athletes. One of the way for that by new coach is two way andsupportive relation and that called interpersonal communication. This researchaims to determine the effectiveness and resistance of coaches in conductinginterpersonal communication in The Ministry For Youth and Sports in Riau.This research uses descriptive qualitative method with the selection ofinformants using purposive sampling technique that selects five selectedinformants, namely 1 badminton coach and 4 badminton athletes whoparticipated in the event of National Students Sports Competition in September2015 ago. The data collecting techniques were by interview, observation anddocumentation. Meanwhile, the techniques of data analysis refer to the interactivemodel of Huberman and Miles. To check the validity of the data, the extension ofparticipation and triangulation techniques have been applied.The results of this study show that the effectiveness of interpersonalcommunication between coaches and athletes badminton is quite effective. Theexplain about quite effective in the results was found barriers, nevertheless theaims still apllied. As for barriers in interpersonal communication betweencoaches and athletes badminton in improving achievement are human andpsychological barriers. As for human barriers concerning human intelligence andthe intelligence of the athletes in interpreting and applying the message given bythe coach, while, for the psychological barriers regarding the various charactersof each and every athlete. As for physcial barriers concerning facilities daninfrastructure scant fulfill provision rule from badminton.Keyword :Interpersonal communication, badminton, athletes, coach.